A Study on the Structural Analysis of Ultra-Lightweight Two-axis Stabilizer for MultiPurpose Tracking (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This is a study on the structural analysis to improve the precise location tracking of the Electro-Optical Tracking System (EOTS), which is installed on a drone to monitor and track a target and calculate the coordinates of the target. The dynamic mass imbalance due to the difference between the center of gravity and the rotation center of the sensor module installed in the EOTS and the friction torque generated in the bearing connected to the BLDC motor to operate the EOTS adversely affects the control performance of the EOTS. However, it is difficult to accurately predict the EOTS stabilization error due to nonlinearity taking into account structural complexity and friction. Therefore, it is intended to minimize stabilization errors through predictable boundary conditions and vibration mode analysis due to disturbances using Ansys structural analysis program.